Association of Genes Involved in the Metabolic Pathways of Amyloid-β and Tau Proteins With Sporadic Late-Onset Alzheimer’s Disease in the Southern Han Chinese Population - Xiao, Xuewen; Jiao, Bin; Liao, Xinxin; Zhang, Weiwei; Yuan, Zhenhua; Guo, Lina; Wang, Xin; Zhou, Lu; Liu, Xixi; Yan, Xinxiang; Tang, Beisha; Shen, Lu (Frontiers in Aging Neuroscience, 2020)
The genes involved in the metabolic pathways of amyloid-β (Aβ) and tau proteins significantly influence the etiology of Alzheimer’s disease (AD). Various studies have explored the associations between some of these genes and AD in the Caucasian population; however, researches regarding these associations remain limited in the Chinese population. To systematically evaluate the associations of these genes with AD, we investigated 19 genes involved in the metabolism of Aβ and tau based on previous studies selected using the PubMed database. This study included 372 patients with sporadic late-onset AD (sLOAD) and 345 cognitively healthy individuals from southern China. The results were replicated in the International Genomics of Alzheimer’s Project (IGAP). Protein-protein interactions were determined using the STRING v11 database. We found that a single nucleotide polymorphism, rs11682128, of BIN1 conferred susceptibility to sLOAD after adjusting for age, sex, and APOE ε4 status and performing the Bonferroni correction (corrected P=0.000153, odds ratio [OR] (95% confidence interval [CI])=1.403(1.079-1.824)), which was replicated in the IGAP. Protein-protein interactions indicated that BIN1 was correlated with MAPT. Moreover, rare variants of NEP and FERMT2 (0.0026